Emprendimientos productivos en economías rurales de los recintos estrella grande, la mariana y la cabecera cantonal del cantón mocache año 2021. - Egas Ochoa, Edison David (2022)
Productive ventures linked to the concept of sustainable tourism as an alternative to community development are an opportunity to improve the standard of living of the population in both rural and urban areas, this research work an initial diagnosis of productive ventures with tourism potential in the Estrella Grande, La Mariana and part of the cantonal capital of the Mocache canton; same that have been identified by each social group taking into consideration their geographical location, their customs, the existing infrastructure and the ideas expressed by the population of each sector. For the execution of any productive activity it is necessary to have basic knowledge about the business models that can be applied, the sustainable forms of agro-tourism production and to know in the territory the motivation that the habitants have to assume the challenge of undertaking in the tourism, artisanal sector and gastronomy of the canton; In addition to knowing the initial infrastructure that is available and the needs of each of the sectors, the level of technical and financial training of those involved to date is measured; since they are the bases for this project to be sustainable and sustainable over time, so that in its future execution it generates direct and indirect income, improving the economy of the aforementioned sectors. It is necessary to emphasize that we want to achieve sustainable tourism linked to the culture of each area, so that it is economically viable and that the natural heritage is not negatively affected or transformed by the influx of tourists to places of interest.